Pengaruh Struktur Kepemilikan dan Debt Covenant Terhadap Konservatisme Akuntansi - Jao, Robert; Ho, Devina (JURNAL RISET AKUNTANSI JAMBI, 2019)
This study aims to examine the effect of managerial ownership, institutional ownership, and debt covenant on accounting conservatism. The population in this study is a non-financial company listed on the Indonesia Stock Exchange (IDX). The number of observations of this research is 682 data year company. The sampling technique used is purposive sampling. Data analysis used is multiple regression analysis method. The empirical results of this study indicate that managerial ownership and debt covenant has a positive and significant effect on accounting conservatism; while institutional ownership has a positive and not significant effect on accounting conservatism. The results of this study can be a consideration for investors to assess the application of accounting conservatism in the preparation of financial statements in making the right investment decisions.